Correction: A mechanistic understanding of the degradation of trace organic contaminants by UV/hydrogen peroxide, UV/persulfate and UV/free chlorine for water reuse. Issue 2 (7th February 2017) - Li, Wei; Jain, Tushar; Ishida, Kenneth; Remucal, Christina K.; Liu, Haizhou
Abstract : Correction for 'A mechanistic understanding of the degradation of trace organic contaminants by UV/hydrogen peroxide, UV/persulfate and UV/free chlorine for water reuse' by Wei Li et al., Environ. Sci.: Water Res. Technol., 2017, 3, 128–138.